Психолого-педагогические методы работы в детских образовательных учреждениях - Казакова, О.В. (My University, 2016)
Article is devoted to application of innovative psihologo-pedagogical methods of work in children's educational institutions. Such methods as fairy tales, outdoor games, psychogymnastic etudes, elements of art therapy and others are considered.
Keywords: psychology; innovation; the children; the game